Ежик в тумане: сказки / С. Г. Козлов - Козлов Сергей Григорьевич (Внеклассное чтение, 2005)
2-3кл Экземпляры: (20210311) / Инвентарный номер: 33541 / Цена: 22.55 / Сис.шифр: Р2 / Авт.знак: К 59 / ГРНТИ: 17 / ББК: 84(2Рос)